Students' conceptualization of culture and diversity with a simulated client. Issue 6 (2nd November 2022) - Kourgiantakis, Toula; Sanders, Jane; Sewell, Karen M.; Asakura, Kenta; Bogo, Marion
ABSTRACT: Teaching students about culture and diversity in social work practice is a complex and important task for social work educators. In this study, we assessed students' conceptualization of culture and diversity factors following a simulated interview. Participants (N = 57 MSW students) completed a reflection questionnaire post-simulation and we conducted thematic analysis of the data. Three themes emerged: 1) culture and diversity impacted the interview, 2) culture and diversity didn't really impact the interview, but …, and 3) culture and diversity didn't really impact the interview. The results indicate it is important to enhance teaching methods related to culture and diversity, and simulation is a promising innovation to prepare students for practice.